Pengaruh Corporate Governance, Profitabilitas, Capital Intensity, Ukuran Perusahaan Terhadap Manajemen Pajak - Siroj Tholibin; Dirvi Surya Abbas; Hamdani Hamdani; Imam Hidayat (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
The purpose of this study was to determine the effect of corporate governance, profitability, capital intensity, company size on manufacturing companies listed on the Indonesia Stock Exchange. The time period used is 7 years, namely 2015-2021. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2021 period totaling 125 companies and a sample of 25 companies was obtained using the purposive sampling method. The number of observational data is 125 data. The type of data used is secondary data. The research method used is panel data regression analysis assisted by the Eviews 9 program. The results of this study indicate that partially independent commissioners have a positive effect on tax management, profitability has no effect on tax management, capital intensity has no effect on tax management, and size has no effect on tax management